Transoceanic Disperse of the White-lipped Island Pit Viper (Cryptelytrops insularis; Kramer,1997) from Sundaland to Lesser Sunda, Indonesia - Priambodo, Bagus; Liu, Fu-Guo Robert; Kurniawan, Nia (The Journal of Experimental Life Science, 2019)
White-lipped island pit viper (Cryptelytrops insularis) is one of the most distributed Viperidae in Indonesia, especially in eastern part of Sundaland and Lesser Sunda. To investigate the evolutionary history and the dispersal pattern of C. insularis, we collected 23 samples from 11 localities. Four simultaneous genes composing two mitochondrial genes (16S rRNA & ND4) and two nuclear genes (7IβFIB & 3ITBP) have been successfully amplified and sequenced. Bayesian inference was performed to reconstruct the phylogeny tree. Furthermore, time divergence and the population demography analyses were estimated. The phylogeny tree of C. insularis exhibits monophyletic group, with four geographically structured lineages. The time divergence estimation indicated that C. insularis evolved at approximately 7 million years ago (mya). Population demography was inferred by Bayesian Skyline Plot analysis, it shows that the population increased constantly from the past to recent time. The evolutionary history of C. insularis can be explained by a pattern of the time divergences estimation that indicating movement from West (Java) to East (Lesser Sunda). We expected that the dispersal factor of C. insularis into many different islands (in Lesser Sunda) is caused by the animal helped and also oceanic rafting which could be the stepping stones to another island.  Keywords: Cryptelytrops insularis, dispersal patterns, phylogeny, population demography, time divergence